Medicinal plants used by women in quilombola communities in the Recôncavo Baiano - Farias, Polianna dos Santos de (2021)
The recovery and maintenance of traditional knowledge associated with the use of medicinal plants is essential for traditional communities, such as quilombola peoples, especially because these resources are easily accessible, often being the main means of health care. Thus, the objective was to carry out a survey of medicinal plants used by women in quilombola communities in Bahia's Recôncavo region. The work was carried out in four communities: Engenho da Cruz, Mutecho Acutinga, Terreno do Governo and Guaruçu, in the municipalities of Cachoeira, São Félix and Maragogipe, in Bahia's Recôncavo. Data were collected from an intentional non-probabilistic sampling with semi-structured interviews with 25 quilombola women who are part of Solidarity Economy Enterprises in their respective communities. Forty plant species were cited as a medicinal resource. Lippia alba (Lemon balm, Verbenaceae) was the most cited species (n = 22), being present in 22 backyards. The leaves stood out as the most used plant structure for oral use in the form of tea. Among the research participants, medicinal plants offer opportunities for health care, findings that suggest their biocultural importance.